To solve the system of equations using elimination, we start with the two equations:
- \(-x + 6y = 13\) (Equation 1)
- \(4x - 10y = -10\) (Equation 2)
First, we can multiply Equation 1 by 4 to align the coefficients of \(x\):
\[ 4(-x + 6y) = 4(13) \] \[ -4x + 24y = 52 \quad \text{(Equation 3)} \]
Now our system of equations is:
- \(-4x + 24y = 52\) (Equation 3)
- \(4x - 10y = -10\) (Equation 2)
Next, we add Equation 3 and Equation 2:
\[ (-4x + 24y) + (4x - 10y) = 52 - 10 \] \[ (24y - 10y) = 42 \] \[ 14y = 42 \] \[ y = 3 \]
Now that we have \(y\), we substitute \(y = 3\) back into one of the original equations to find \(x\). We can use Equation 1:
\[ -x + 6(3) = 13 \] \[ -x + 18 = 13 \] \[ -x = 13 - 18 \] \[ -x = -5 \] \[ x = 5 \]
So the solution to the system of equations is:
\[ (x, y) = (5, 3) \]
Final Answer: \((5, 3)\)